2020
DOI: 10.1029/2019jb018284
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Spectral Distortion of Local Volcano Infrasound by Nonlinear Propagation at Sakurajima Volcano, Japan

Abstract: Sound waves generated by erupting volcanoes can be used to infer important source dynamics, yet acoustic source‐time functions may be distorted during propagation, even at local recording distances ( <15 km). The resulting uncertainty in source estimates can be reduced by improving constraints on propagation effects. We aim to quantify potential distortions caused by wave steepening during nonlinear propagation, with the aim of improving the accuracy of volcano‐acoustic source predictions. We hypothesize that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 100 publications
(226 reference statements)
4
38
0
Order By: Relevance
“…We note that peak pressures at CLES do not appear to strongly correlate with seismo-acoustic time lags ( Figure 7D), indicating that nonlinear propagation (if present) has minimal effect on the seismio-acoustic time lag for Cleveland explosions. This is consistent with the findings of Maher et al (2020), where nonlinear propagation was found to be a secondary effect on the observed waveform. However, it does appear that the highest peak pressures and those that clipped the infrasound sensor ( Figure 7D, open circles) had lower seismo-acoustic time lags.…”
Section: Nonlinear Propagationsupporting
confidence: 93%
See 3 more Smart Citations
“…We note that peak pressures at CLES do not appear to strongly correlate with seismo-acoustic time lags ( Figure 7D), indicating that nonlinear propagation (if present) has minimal effect on the seismio-acoustic time lag for Cleveland explosions. This is consistent with the findings of Maher et al (2020), where nonlinear propagation was found to be a secondary effect on the observed waveform. However, it does appear that the highest peak pressures and those that clipped the infrasound sensor ( Figure 7D, open circles) had lower seismo-acoustic time lags.…”
Section: Nonlinear Propagationsupporting
confidence: 93%
“…Nonlinear propagation modeling results for a synthetic receiver at 3.8 km from the source (slant distance from the Cleveland summit to station CLES) show the expected distortion due to increasingly nonlinear propagation ( Figures 7B,C). As the source pressure increases, the compression travels faster while the rarefaction travels relatively slower, similar to results in Maher et al (2020). Therefore, the arrival time of the peak compression decreases with higher source pressure ( Figure 7C).…”
Section: Nonlinear Propagationsupporting
confidence: 72%
See 2 more Smart Citations
“…Iezzi et al 2019a;Johnson and Miller 2014;Kim et al 2015], vent radius [Muramatsu et al 2018], and crater geometry [Johnson et al 2018a;Johnson et al 2018b], but wavefield interactions with topography lead to variable source estimates from signals recorded at different azimuths [e.g. Iezzi et al 2019a;Kim and Lees 2014;Lacanna and Ripepe 2013;Maher et al 2020;McKee et al 2014].…”
Section: Introductionmentioning
confidence: 99%